Residential Field Site Training Programme Abstracts: 49th Batch, Session: 2006-2007, 4th year MBBS Students, CMC - Editor, The (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i2.7740 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):50-53